The Prevalence and Association between Subclinical Hypothyroidism and Gall Stone Disease: Study in Shaheed Suhrawardy Medical College Hospital (Journal of Shaheed Suhrawardy Medical College, 2020)
Background: Gall stones are the most common biliary pathology. Subclinical hypothyroidism is not an uncommon problem in the population with thyroid disease, several explanations for a possible relation between hypothyroidism and lipid metabolism with gall stone formation proved that prevalence of gall stones is increased in patients with hypothyroidism.Objective: To find the prevalence and correlation between the subclinical hypothyroidism and gall stone disease.Methods: This is a cross-sectional study was done in the Unit-II of department of Surgery of Shaheed Suhrawardy Medical Hospital between July 2018 to June 2019, where 80 patients presented with gall stones. All the patients were assessed and prepared for cholecystectomy by detailed history, clinical examination, thyroid function test, abdominal ultrasound and others investigation needed for general anaesthesia.Results: Among 80 patients, 78.57% were in 40–59 year age group, 56 (70%) of them were female and 24 (30%) were male. Of the total number of patients, 14 of them (17.5%) had subclinical hypothyroidism and 66 (82.5%) were euthyroid. Most of patients in the subclinical hypothyroid group were showing female gender predominance with 78.57%. While the prevalence among males were found 21.43%. Dyslipidemia was present among 81.25% patients (p=0.03) having subclinical hypothyroidism and gall stones. Besides single stone was common (57.14%) among this hypothyroid group and all stones of this group were >1 cm.Conclusion: There is a gender speciûc relationship between subclinical hypothyroidism and gall stone disease. As this study sharing statistically significant in the prevalence of the subclinical hypothyroidism among females in age groupe³40 years, dyslipidemia and single gall stone. This subset of patients should be assessed for thyroid dysfunction.J Shaheed Suhrawardy Med Coll, December 2019, Vol.11(2); 130-133